Novel low-fouling membranes from lab to pilot application in textile wastewater treatment - Galiano, Francesco; Friha, Ines; Deowan, Shamim Ahmed; Hoinkis, Jan; Xiaoyun, Ye; Johnson, Daniel; Mancuso, Raffaella; Hilal, Nidal; Gabriele, Bartolo; Sayadi, Sami; Figoli, Alberto (Journal of colloid and interface science, 2018)
[Display omitted] A novel antifouling coating based on the polymerization of a polymerisable bicontinuous microemulsion (PBM) was developed and applied for commercially available membranes for textile wastewater treatment. PBM coating was produced by polymerizing, on a polyethersulfone (PES) membrane, a bicontinuous microemulsion, realized by finely tuning its properties in terms of chemical composition and polymerization temperature. In particular, the PBM was prepared by using, as the surfactant component, inexpensive and commercially available dodecyltrimethylammonium bromide (DTAB). The coating exhibited a more hydrophilic and a smoother surface in comparison to uncoated PES surface, making the produced PBM membranes more resistant and less prone to be affected by fouling. The anti-fouling potential of PBM membranes was assessed by using humic acid (HA) as a model foulant, evaluating the water permeability decrease as an indicator of the fouling propensity of the membranes. PBM membrane performances in terms of dye rejection, when applied for model textile wastewater treatment, were also evaluated and compared to PES commercial ones. The PBM membranes were finally successfully scaled-up (total membrane area 0.33 m2) and applied in a pilot membrane bioreactor (MBR) unit for the treatment of real textile wastewater.